Ultrasensitive terahertz sensing of gold nanoparticles inside nano slot antennas - Ryu, Yong-Sang; Lee, Dong-Kyu; Kang, Ji-Hun; Lee, Sang-Hun; Yu, Eui-Sang; Seo, Minah (OPTICAL SOC AMER, 2017)
We introduce a robust control method of terahertz (THz) transmission by tuning filling factors of Au nanoparticles (AuNPs) inside nano slot antennas. AuNPs in sub-100 nm diameters were spread over the nano slot antennas, followed by sweeping them into the slots. AuNPs can be efficiently localized and inserted into nano slots where the THz fields are greatly enhanced, by a "squeegee" made of the polydimethylsiloxane (PDMS). The sweeping of the AuNPs results in further dramatic reduction of THz transmission by suppressing the fundamental resonance mode of the nano slot, as compared to a typical random dropping case. It definitely works for an accurate THz transmission control, as well as the removal of unwanted ions that occasionally confuse signal accuracy from the target signals. Our approach provides a complete reinterpretation of sample deposition for further steady demands in developing ultrasensitive terahertz (THz) molecule sensors. (C) 2017 Optical Society of America
Keywords: TIME-DOMAIN SPECTROSCOPY; ABSORPTION; PARAMETERS